Changes in corneal curvature and astigmatism in senile cataract patients after phacoemulsification - Xiao, Yan-Hui; Liu, Yue-Qi; Chen, Zhi-Gang (Frontiers in Medicine, 2024)
Purpose: Analysis of changes in corneal curvature and astigmatism after phacoemulsification for senile cataracts. Methods: Retrospective collection of clinical data from patients who underwent uncomplicated phacoemulsification at the First Affiliated Hospital of Soochow University. The changes in total corneal curvature, anterior surface curvature, posterior surface curvature, and astigmatism were measured by the Sirius system. The axial length was measured by Lenstar 900. Results: The total corneal curvature and anterior surface curvature at 3 months were all larger than those before phacoemulsification, and the difference was statistically significant (P<0.05). Compared with preoperative results, there was no significant change in corneal posterior surface curvature and astigmatism three months after surgery (P>0.05). Changes in corneal curvature and astigmatism were not significantly correlated with age at 3 months after surgery (P>0.05).Postoperative astigmatism was increased with the growth of axial length, while corneal curvature was decreased (P<0.05). Conclusion: Phacoemulsification can lead to increased postoperative corneal curvature in elderly cataract patients, and with the growth of the axial length, the corneal astigmatism was increased.